Genotypic and phenotypic modifications of Neisseria meningitidis after an accidental human passage - Omer, H; Rose, G; Jolley, K; Frapy, E; Zahar, JR; Maiden, M; Bentley, S; Tinsley, C; Nassif, X; Bille, E (Public Library of Science, 2011)
A scientist in our laboratory was accidentally infected while working with Z5463, a Neisseria meningitidis serogroup A strain. She developed severe symptoms (fever, meningism, purpuric lesions) that fortunately evolved with antibiotic treatment to complete recovery. Pulse-field gel electrophoresis confirmed that the isolate obtained from the blood culture (Z5463BC) was identical to Z5463, more precisely to a fourth subculture of this strain used the week before the contamination (Z5463PI). In order to get some insights into genomic modifications that can occur in vivo, we sequenced these three isolates. All the strains contained a mutated mutS allele and therefore displayed an hypermutator phenotype, consistent with the high number of mutations (SNP, Single Nucleotide Polymorphism) detected in the three strains. By comparing the number of SNP in all three isolates and knowing the number of passages between Z5463 and Z5463PI, we concluded that around 25 bacterial divisions occurred in the human body. As expected, the in vivo passage is responsible for several modifications of phase variable genes. This genomic study has been completed by transcriptomic and phenotypic studies, showing that the blood strain used a different haemoglobin-linked iron receptor (HpuA/B) than the parental strains (HmbR). Different pilin variants were found after the in vivo passage, which expressed different properties of adhesion. Furthermore the deletion of one gene involved in LOS biosynthesis (lgtB) results in Z5463BC expressing a different LOS than the L9 immunotype of Z2491. The in vivo passage, despite the small numbers of divisions, permits the selection of numerous genomic modifications that may account for the high capacity of the strain to disseminate.